Prevalence of anogenital warts in men with HIV/AIDS and associated factors - De Camargo, Caio Cavassan [UNESP]; Tasca, Karen Ingrid [UNESP]; Mendes, Monica Banwart [UNESP]; Miot, Hélio Amante [UNESP]; De Souza, Lenice Do Rosário [UNESP] (My University, 2015)
Background: Infection with human papilloma virus (HPV) is the most common sexually transmitted disease in the world. Among the 630 million new cases of HPV that occur each year, 30 million develop anogenital warts. Although subclinical infection with HPV is the most common cause, genital warts are also associated with immunosuppression caused by HIV. In view of the high prevalence of HPV/HIV co-infection particularly among men who have sex with men, the objectives of this study were to determine the prevalence of anogenital warts in men with HIV/AIDS and to identify associated factors. Methods: A cross-sectional study was conducted on 159 men with HIV/AIDS consecutively selected at a referral service in Botucatu, São Paulo, Brazil, in which the association between sociodemographic, behavioral and clinical variables and the presence of anogenital warts was evaluated. After hierarchical analysis of the data, variables presenting a p value = 0.2 were entered into an unconditional multivariate logistic regression model. Results: Forty-nine (31%) of the HIV-positive patients had anogenital warts. The mean age was 44.6 ± 9.6 years. The main factors associated with the presence of anogenital warts were irregular antiretroviral treatment and genital herpes(HSV). Conclusion: The present study demonstrate that anogenital warts occur in almost one-third of the male population infected with HIV and factors associated with a higher risk of being diagnosed with anogenital warts were irregular cART use and co-infection with HSV, other variables could not be associated.
Keywords: AIDS; Anogenital warts; CD4+ T lymphocytes; HPV; Men